2017
DOI: 10.17221/99/2016-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunocastration on growth performance, body composition, meat quality, and boar taint

Abstract: Stupka R., Čítek J., Vehovský K., Zadinová K., Okrouhlá M., Urbanová D., Stádník L. (2017): Effects of immunocastration on growth performance, body composition, meat quality, and boar taint. Czech J. Anim. Sci., 62, 249-258.The study objective was to evaluate the effect of immunocastration in the period between the first and second vaccinations and subsequently between the second vaccination and slaughter on growth performance, carcass composition, meat quality, and boar taint, and compare results in immunocas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
(34 reference statements)
2
6
0
Order By: Relevance
“…Significant differences ( p < 0.05) between different sire lines in pH 45 were observed (i.e., the highest values in C and the lowest in B); however, no differences could be found between different male categories for this trait. In agreement with the results of this study, the results of the three meta-analyses showed no or very small difference between different male categories in the case of muscle pH, indicating this trait to be without actual practical importance in regard to sex categories [ 7 , 26 , 32 , 65 ]. We also found a significant interaction ( p < 0.001) between the TSL*MC on initial pH values ( Figure 2 A; Table S1 ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Significant differences ( p < 0.05) between different sire lines in pH 45 were observed (i.e., the highest values in C and the lowest in B); however, no differences could be found between different male categories for this trait. In agreement with the results of this study, the results of the three meta-analyses showed no or very small difference between different male categories in the case of muscle pH, indicating this trait to be without actual practical importance in regard to sex categories [ 7 , 26 , 32 , 65 ]. We also found a significant interaction ( p < 0.001) between the TSL*MC on initial pH values ( Figure 2 A; Table S1 ).…”
Section: Resultssupporting
confidence: 90%
“…Similar to the result for animals originating from TSL B, in the investigation of Škrlep et al (2011) [ 43 ] on two types of crossbreds (Duroc and Pietrain sired), drip loss measured after 24 h and 48 h was also influenced by sex and crossbreed type interaction but without any differences between the MCs. The results of individual studies investigating only the sex type as an influential factor are ambiguous; however, generally, no difference between different sex types was found for this trait [ 7 , 32 , 49 ]. It should be noticed that observed drip loss was quite high in all investigated groups; however, this may be more related to the relatively low age of the animals, especially for entire males, which still did not manage to exhibit their full physiological potential at this stage of growth and development [ 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower ADG in IM than in SCM might be due to a lower feed intake; it was not recorded in the present trial but it has been observed by other authors [14,15]. This effect has also been found when entire males and SCM were compared [16][17][18], which could be related to higher levels of testicular hormones in entire males than in SCM [19]. Cronin et al [20] have reported more aggressive and sexual behaviors in entire males, which would reduce their eating times.…”
Section: Growth Performancesupporting
confidence: 71%
“…Immunocastration is based on vaccination against gonadotropin-releasing hormone (GnRH), which leads to inhibition of luteinising hormone (LH) and subsequently elimination of androstenone—one of the two main compounds responsible for boar taint [ 1 , 2 ]. The effect of immunocastration on various aspects of entire male production has recently been the subject of extensive research, e.g., on growth intensity, carcass performance and meat quality [ 3 , 4 , 5 , 6 , 7 ], fatty acid composition in muscle or subcutaneous fat [ 8 , 9 , 10 , 11 ], sensory characteristics and consumer´s acceptance of meat [ 12 , 13 ], or boar taint compounds [ 14 , 15 ]. Fattening entire males might also become a suitable alternative because of some advantages of boars over surgical castrates such as greater growth intensity, better feed conversion, and higher lean meat content in carcass.…”
Section: Introductionmentioning
confidence: 99%